Comparative Study on Muscle Fiber Types of Longissimus Dorsi of Xinjiang Brown Cattle and Angus Cattle of Different Months - Ya-wei Sun; Miao Qu; Jiayinaguli Tuersunbai; Xuan-yi Wang; Tuolihanayi Tuoliken; Xiao-hong Zhang; Gang Yao; Huijun Shi (Journal of Food Quality)
The longissimus dorsi muscle of Xinjiang brown cattle and Angus cattle at the age of 3, 7, 12, and 24 months under the same feeding and management conditions were selected to explore the differences of muscle 4 fiber types in this study. The muscle histological and molecular biological reasons for the quality difference between Xinjiang brown cattle and Angus beef were discussed. The morphology of the muscle was compared by ATP enzyme staining and SDH enzyme staining, and its gene expression was detected by qRT-PCR. The mRNA expression levels of Myhc-I in 3-month-old Xinjiang brown cattle were significantly higher than those in Angus cattle of the same age (P<0.01). The 4 fiber types of 7-month-old Xinjiang brown cattle were significantly lower than those of Angus cattle of the same age (P<0.01). The expression level of type I and IIb in 12-month-old Xinjiang brown cattle was significantly higher than that in 12-month-old Angus cattle (P<0.05). Type I and IIa of 24-month-old Xinjiang brown cattle were significantly lower than those of Angus cattle of the same age (P<0.05). However, in our study, the basic characteristics of longissimus dorsi of Xinjiang brown cattle and Angus cattle, such as color, pH, shearing force, and other characteristics were not detected, which is lacking in this aspect. Overall, with the increase of age, the growth trend of muscle fiber morphology of Xinjiang brown cattle and Angus cattle is roughly the same, but from the point of view of muscle fiber types, the Xinjiang brown cattle are more suitable for the production of early fat calves and to make some reference for improving the quality of beef cattle in China.